2014
DOI: 10.1088/1475-7516/2014/08/038
|View full text |Cite
|
Sign up to set email alerts
|

Detecting non-relativistic cosmic neutrinos by capture on tritium: phenomenology and physics potential

Abstract: We study the physics potential of the detection of the Cosmic Neutrino Background via neutrino capture on tritium, taking the proposed PTOLEMY experiment as a case study. With the projected energy resolution of ∆ ∼ 0.15 eV, the experiment will be sensitive to neutrino masses with degenerate spectrum, m 1 m 2 m 3 = m ν 0.1 eV. These neutrinos are non-relativistic today; detecting them would be a unique opportunity to probe this unexplored kinematical regime. The signature of neutrino capture is a peak in the el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
268
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(273 citation statements)
references
References 137 publications
(224 reference statements)
5
268
0
Order By: Relevance
“…Recently it has been suggested that measurements of the relic neutrino abundance could discriminate between Dirac and Majorana neutrinos due to their different projected count-rates for PTOLEMY of ∼ 4 yr −1 and ∼ 8 yr −1 , respectively [4]. We see that this proposal may not work in the presence of additional non-thermal Dirac neutrinos which could increase the respective count rate by 64% thereby diminishing the difference between Dirac and Majorana neutrinos.…”
Section: Detection Of a Non-thermal Neutrino Backgroundmentioning
confidence: 69%
See 2 more Smart Citations
“…Recently it has been suggested that measurements of the relic neutrino abundance could discriminate between Dirac and Majorana neutrinos due to their different projected count-rates for PTOLEMY of ∼ 4 yr −1 and ∼ 8 yr −1 , respectively [4]. We see that this proposal may not work in the presence of additional non-thermal Dirac neutrinos which could increase the respective count rate by 64% thereby diminishing the difference between Dirac and Majorana neutrinos.…”
Section: Detection Of a Non-thermal Neutrino Backgroundmentioning
confidence: 69%
“…Since the thermal neutrinos propagate as mass eigenstates, the different flavors will, to a good approximation, be equilibrated at late times [4]. We further assume that the flavor composition of the non-thermal neutrinos is also roughly 1 : 1 : 1.…”
Section: Detection Of a Non-thermal Neutrino Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalization to the case of interest, ν j + 3 H → 3 He + e − , is straightforward and will be addressed afterwards (see [7,12,13] for previous calculations of the unpolarized capture rate). The neutron and neutrino are prepared in definite spin states, while the spins of the proton and electron are not observed.…”
Section: Polarized Scattering Amplitudementioning
confidence: 99%
“…Their planned target consists of ∼100 g of tritium ( 3 H) atomically bound to graphene. PTOLEMY should observe ∼10 CνB capture events per year, depending on the mass hierarchy and the Dirac versus Majorana nature of the neutrinos; the rate is half as large for non-relativistic Dirac neutrinos [7]. PTOLEMY has a planned energy resolution ∼0.15 eV, though this resolution may be further improved [6].…”
mentioning
confidence: 99%